A Case for Thinking Without Consciousness. (January 2016) - Dijksterhuis, Ap; Strick, Madelijn
People can engage in prolonged thought processes, such as when they are facing an important decision or when they are working on a scientific discovery. Such thought processes can take months or even years. We argue that while people engage in such thinking, they make progress not only when they consciously think but also sometimes when they are consciously thinking about something else—that is, while they think unconsciously. We review the literature on unconscious thought (UT) processes and conclude that there is indeed quite some evidence for UT. Conceptualized as a form of unconscious goal pursuit, UT is likely to be especially fruitful for thought processes that are complex, important, or interesting to the thinker. In addition, we discuss other characteristics of the UT process. We end with proposing Type 3 processes, in addition to Type 1 and Type 2 (or Systems 1 and 2) processes, to accommodate prolonged thought processes in models on thought.